2022
DOI: 10.1039/d2ee00731b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient interconnecting layers in monolithic all-perovskite tandem solar cells

Abstract: Tandem solar cells (TSCs) are widely recognized as an effective device architecture to overcome the spectral loss in single-junction solar cells and surpass the Shockely-Queisser (SQ) limit. Organic–inorganic hybrid perovskites...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 93 publications
0
37
0
Order By: Relevance
“…So far, perovskite solar cells (PSCs) have become the most promising material for optoelectronic devices due to their excellent properties of such as high absorption coefficient, long carrier diffusion length, simple fabrication, and tunable bandgap. [1][2][3][4][5][6][7][8][9][10][11] Thereinto, the power conversion efficiency (PCE) of single-junction PSCs has achieved a great rising from 3.8% to 25.7%, which almost approaches the level of monocrystalline silicon. [12] Hence, apart from the high efficiency, device stability has become more and more important for further development.…”
Section: Introductionmentioning
confidence: 99%
“…So far, perovskite solar cells (PSCs) have become the most promising material for optoelectronic devices due to their excellent properties of such as high absorption coefficient, long carrier diffusion length, simple fabrication, and tunable bandgap. [1][2][3][4][5][6][7][8][9][10][11] Thereinto, the power conversion efficiency (PCE) of single-junction PSCs has achieved a great rising from 3.8% to 25.7%, which almost approaches the level of monocrystalline silicon. [12] Hence, apart from the high efficiency, device stability has become more and more important for further development.…”
Section: Introductionmentioning
confidence: 99%
“…In general, spin-coating processes using nonvolatile polar solvents, such as dimethyl sulfoxide (DMSO) and N,N -dimethyl­formamide (DMF), are used to fabricate highly efficient PVSK films for multijunction devices. , These solvents readily penetrate the interfacial layers between two PVSK films during the second spin-coating process, leading to the partial dissolution of the underneath PVSK layer . It was also reported that the residual nonvolatile solvents still exist in the thin film even after the drying process due to the formation of a PVSK–solvent intermediate phase. , Depositing a dense oxide interlayer via atomic layer deposition (ALD) is a proven way to prevent the degradation of the underneath PVSK layer. However, the ALD process with a slow growth rate requires a long process time, potentially increasing the fabrication cost and causing damage to the PVSK cell due to the oxidizing agent and the high process temperature. Another way to avoid the solvent-related degradation of the underneath PVSK layer is to adopt vacuum deposition techniques, , but no study has so far demonstrated the successful vacuum deposition of an upper PVSK layer on another PVSK layer.…”
mentioning
confidence: 99%
“…93 Particularly in all-perovskite TSCs, ICL should also act as a protection layer to prevent the deterioration of the pre-deposited subcell from the solution process of subsequent perovskite layer fabrication. 94 Because two or more cells in 2-T tandem devices are connected in series, the J sc of the tandem devices is limited by the lower one. The precise matching of J sc by controlling the thickness and bandgap of perovskite films is important to improve the overall current of the tandem devices.…”
Section: Halide Perovskite Solar Cellsmentioning
confidence: 99%